The Intercultural Dimension of EFL in the Algerian Middle School - Wahid Hamza Mohamed CHAMI (Altralang Journal)
This article provides a comprehensive overview of the current state of intercultural competence in English as Foreign Language (EFL) settings in Algeria. The author argues that there is an increasing demand for the integration of culture in EFL and that this integration must encompass both the big "C" and small "c" aspects of culture, as well as the source and target cultures. The article examines the Algerian curriculum and the practices of teachers about intercultural competence trying to find a room for improvement. The article also provides a detailed analysis of the place of culture in Algerian English textbooks, highlighting the importance of incorporating cultural content in language learning materials. Overall, this article makes a compelling case for the integration of intercultural competence in EFL settings in Algeria and provides significant insights into the eventual challenges for culture instruction in EFL context.